Effectiveness of Instagram Videos in Increasing Interest in Arabic Language Learning at Madrasah Aliyah Negeri Kutai Barat - Muhammad Iberahim Mahmud; Syarifaturrahmatullah Syarifaturrahmatullah (El-Syaker : Samarinda International Journal of Language Studies, 2024)
Students' interest in learning is still a problem that is often faced in learning Arabic, including in Madrasah Aliyah Negeri (MAN) Kutai Barat. To overcome this, the researcher offers the use of Instagram video media as a learning media in increasing students' interest in learning. This study aims to determine whether the use of Instagram videos is effective in increasing students' interest in learning Arabic at MAN Kutai Barat. This research is a quantitative research, with the type of research Quasi Experimental Type Nonequivalent Control Group Design. The population of this study were all students of MAN Kutai Barat using purposive sampling, the samples of this study were X IIS class totaling 23 students as the control group and X MIA class totaling 22 students as the experimental group. The instruments of this research are questionnaires and observation sheets. The results showed that the paired sample t-test results obtained a Sig. (2-tailed) of 0.000 <0.05, this indicates that H0 is rejected and Ha is accepted. Based on the calculation of the tcount, the tcount value of the experimental class and control class is 10.799> 3.024 or the experimental class tcount value> control class tcount. And based on the results of the N-Gain calculation, it can be seen that the average N-Gain score in the experimental class is 0.53 which is included in the moderate category with a minimum N-Gain score of 0.29 and a maximum of 0.89. Based on this description, it can be concluded that the use of Instagram videos is effective in the medium category in increasing students' interest in learning Arabic at MAN Kutai Barat.